2014
DOI: 10.1080/02699931.2014.951314
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of excessive engagement in health-related behaviours on disgust propensity

Abstract: The present study examined the extent to which engagement in health-related behaviours modulate disgust propensity, a purportedly stable personality trait. Participants were randomised into a health behaviour (n = 30) or control condition (n = 30). After a baseline period, participants in the health behaviour condition spent one week actively engaging in a clinically representative array of health-related behaviours on a daily basis, followed by a second week-long baseline period. Participants in the control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…This finding is in contrast with the traditional view of DP as a stable personality trait and suggest that the construct have both time-varying and time-invariant components. This view is consistent with previous research showing that excessive engagement in health-related safety behaviors (i.e., hand washing) does significantly increase DP (Olatunji, 2015). These findings also raise the possibility that elevated DP in C-OCD may be a consequence rather than a cause of the disorder.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in contrast with the traditional view of DP as a stable personality trait and suggest that the construct have both time-varying and time-invariant components. This view is consistent with previous research showing that excessive engagement in health-related safety behaviors (i.e., hand washing) does significantly increase DP (Olatunji, 2015). These findings also raise the possibility that elevated DP in C-OCD may be a consequence rather than a cause of the disorder.…”
Section: Discussionsupporting
confidence: 92%
“…Although treatment outcome research suggests that targeting DP during treatment may result in improvements in OCD symptoms, longitudinal research has provided mixed evidence on the extent to which DP causes the development of OCD. Although DP has traditionally been conceptualized as a trait-like personality characteristic, Olatunji (2015) found that selective engagement in health-related behaviors significantly increased DP. This finding suggests that DP is indeed malleable and an alternative hypothesis may be that the presence of OCD symptoms leads to an increase in DP, or at least that DP and OCD symptoms influence each other in a reciprocal fashion similar to the effect observed with other trait-like variables (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Such vigilance is often coupled with maladaptive coping strategies that paradoxically increase levels of disgust proneness. Indeed, research has shown that excessive engagement in safety behaviors like hand washing significantly increases disgust proneness (Olatunji, 2015) and the link between disgust proneness and hand washing is mediated by danger expectancies about disease (Thorpe, Barnett, Friend, & Nottingham, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, although we know that health anxiety is positively correlated with engagement in these behaviors, far less is known about whether each predicts the future occurrence of the other. Outside of an epidemic, one exception is a longitudinal study by Olatunji (2015) in which engagement in health behaviors related to subsequent increases in disgust propensity. However, the extent to which these longitudinal relationships exist in the context of global pandemic remains unknown.…”
Section: Introductionmentioning
confidence: 99%